C.02: CNSS K.G. McKenzie Memorial Prize in Basic Neuroscience Research: Whole genome expression profiling of blood-brain barrier endothelial cells after experimental subarachnoid hemorrhage. (17th June 2016) - Tso, MK; Turgeon, P; Bosche, B; Ai, J; Marsden, P; Macdonald, RL
Abstract : Background: The pathophysiology of subarachnoid hemorrhage (SAH) is complex and includes disruption of the blood-brain barrier (BBB). We freshly isolated BBB endothelial cells (BECs) by 2 distinct methods after experimental SAH and then interrogated their gene expression profiles with the goal of uncovering new therapeutic targets.Methods: SAH was induced using the prechiasmatic blood injection mouse model. BBB permeability studies were performed by administering intraperitoneal cadaverine dye injections at 24h and 48h. BECs were isolated either by sequential magnetic-based sorting for CD45 - CD31 + cells or by fluorescence-activated cell sorting (FACS) for Tie2 + Pdgfrb - cells. Total RNA was extracted and analyzed using Affymetrix Mouse Gene 2.0 ST Arrays.Results: BBB impairment occurred at 24h and resolved by 48h after SAH. Analysis of gene expression patterns in BECs at 24h reveal clustering of SAH and sham samples. We identified 707 (2.8%) significant differentially-expressed genes (403 upregulated, 304 downregulated) out of 24, 865 interrogated probe sets. Many significantly upregulated genes were involved in inflammatory pathways. These microarray results were validated with real-time polymerase chain reaction (RT-PCR).Conclusions: This study is the first to investigate in an unbiased manner, whole genome expression profiling of freshly-isolated BECs in an SAH animal model, yielding targets for novel therapeutic intervention.